Human chorionic gonadotropin promotes murine Treg cells and restricts pregnancy-harmful proinflammatory Th17 responses - Lentz, Lea S.; Stutz, Annika J.; Meyer, Nicole; Schubert, Kristin; Karkossa, Isabel; von Bergen, Martin; Zenclussen, Ana C.; Schumacher, Anne (Frontiers in Immunology, 2022)
An equilibrium between proinflammatory and anti-inflammatory immune responses is essential for maternal tolerance of the fetus throughout gestation. To study the participation of fetal tissue-derived factors in this delicate immune balance, we analyzed the effects of human chorionic gonadotropin (hCG) on murine Treg cells and Th17 cells in vitro, and on pregnancy outcomes, fetal and placental growth, blood flow velocities and remodeling of the uterine vascular bed in vivo. Compared with untreated CD4+CD25+ T cells, hCG increased the frequency of Treg cells upon activation of the LH/CG receptor. hCG, with the involvement of IL-2, also interfered with induced differentiation of CD4+ T cells into proinflammatory Th17 cells. In already differentiated Th17 cells, hCG induced an anti-inflammatory profile. Transfer of proinflammatory Th17 cells into healthy pregnant mice promoted fetal rejection, impaired fetal growth and resulted in insufficient remodeling of uterine spiral arteries, and abnormal flow velocities. Our work show that proinflammatory Th17 cells have a negative influence on pregnancy that can be partly avoided by in vitro re-programming of proinflammatory Th17 cells with hCG.